PROSPECTS FOR THE USE OF ZEOLITE CONTAINING GEOMIN FORTE IN THE TREATMENT OF COVID-19 AND POST COVID-19 CONDITION (World Science, 2022)
The aim of the research was to study and analyze peculiarities and prospects for the use of zeolite containing Geomin Forte in the treatment of covid-19 and post covid-19 condition. Antioxidants are substances that the human body constantly needs in order to maintain it in a normal state, which means maintaining the necessary balance between free oxidative radicals and antioxidant forces, the role of which is played by antioxidants.Vitamin E increases the body's nonspecific resistance, and by activating the synthesis of cytokines, tocopherol stimulates its own anti-inflammatory activity. The effect of vitamin E is to stimulate the reproduction of immune cells, systems that need to quickly multiply when they meet the source of a possible disease. In the body, this process is called mitogenesis.The pharmacodynamic effects of tocopherol are synergistic when combined with vitamins C and A. Retinol provides formation of immune (protective) cells, lining respiratory tract and gastrointestinal tract, serving as a natural barrier to infection. Medicine will enhance possibilities of adaptation of the organism to the changed environment, because, in many cases, it is very difficult to protect the population from the impact of the negative factor (including ionizing radiation, natural disasters, etc.) According the study results “Geomin Forte” can be used during intoxications (used as the best sorbent for food, infectious, occupational intoxications, chronic metals and chronic exposure to radiation). As well as when the functional state of the immune system is impaired and fatigue and as an adjunct for allergic diseases. The mineral zeolite (clinoptilolite), the 500 mg activated clinoptilolite "Geomin Forte" developed by us is characterized by antioxidant action. Unlike the conventional antioxidants, it stimulates the body's endogenous antioxidant system and is a direct-acting oxidoreductive agent. Its activated natural mineral zeolite (clinoptilolite) acts directly on the cell membrane as a surface-active donor of electrons.With its oxidizing effect, "Geomin Forte" is 200 times more than vitamins C and E. Used in combination with antioxidant therapy in the context of standard treatment for the following diseases: Diabetes mellitus, accelerated aging process; alzheimer's disease; parkinson's disease; endocrine pathologies; atherosclerosis and ischemic heart disease, hypertensive disease, stroke, rheumatism.